The resurgence of frugal innovation - Ahuja, Suchit; Cadeddu, Stephanie (R&D Today, 2021)
Frugal Innovation is on the rise with products and services that leverage digital technologies like big data, AI, virtual reality and m-health.
Keywords: Innovation frugale; Libre accès; OBNL